Composite photocatalyst based on carbon nitride surface interface modification, method and application
By introducing nitrogen defects and Ni(OH)2 modifications into the photocatalyst, Ni(OH)2/g-C3N4-x composite material is formed, which solves the limitations of existing photocatalytic hydrogen evolution performance and stability, and achieves efficient and stable photocatalytic hydrogen evolution effect and cost-effective improvement.
Patent Information
- Application Number
- CN202411814610.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing photocatalysts have limitations in photogenerated carrier separation and transfer efficiency, number of active sites, stability and cost, which limit their large-scale application in actual industrial production.
Through the composite photocatalyst preparation method based on the interface modification of carbon nitride, nitrogen defects and Ni(OH)2 modification are introduced to form Ni(OH)2/g-C3N4-x composite material, and a 2D/2D heterojunction structure is constructed to improve photocatalytic performance.
The photocatalytic hydrogen evolution rate and stability of the photocatalyst are significantly improved, and the hydrogen evolution activity is increased by 39.4 times, which widens the light absorption range, reduces the cost of use, and increases its application potential in industrial production.
Smart Images

Figure CN119633872A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic nanocomposite materials, and specifically relates to a method for preparing a composite photocatalyst based on carbon nitride surface interface modification, and also relates to a composite photocatalyst based on carbon nitride surface interface modification and application. Background Art
[0002] Photocatalytic water splitting to produce hydrogen is a highly promising method for hydrogen production, and much research has been devoted to developing efficient semiconductor photocatalysts to achieve this process. However, despite the numerous studies, no catalyst has yet been able to fully meet all the requirements for large-scale practical applications. The development of efficient, stable, and cost-effective photocatalysts for hydrogen production remains an ongoing challenge in this field. This is mainly due to the various limitations of existing photocatalysts in terms of the separation and transfer efficiency of photogenerated carriers, the number of active sites, stability, and cost, which restricts their large-scale application in actual industrial production.
[0003] Graphitic carbon nitride (g-C3N4) has attracted extensive attention in the field of photocatalytic hydrogen evolution due to its advantages such as high cost-effectiveness and easy preparation. However, pure g-C3N4 has some obvious disadvantages, such as fast recombination rate of photogenerated carriers, low electronic conductivity and insufficient active sites, which seriously hinder its further development in practical applications of photocatalytic hydrogen evolution. In order to overcome these problems, researchers have adopted a variety of modification strategies to improve the photocatalytic performance of g-C3N4 under visible light, including metal or non-metal doping, construction of nanostructures, loading of hydrogen evolution co-catalysts and preparation of heterojunctions.
[0004] Introducing vacancies is considered to be one of the effective strategies to narrow the semiconductor band gap, inhibit electron-hole pair recombination, increase the density of active sites, and shorten the carrier and reactant transport paths. 4-x ) exhibits excellent photocatalytic activity in the visible light-driven hydrogen evolution reaction. At the same time, Ni(OH)2 has been used as an effective co-catalyst to enhance the hydrogen evolution rate of various semiconductor photocatalysts. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a composite photocatalyst based on carbon nitride surface interface modification, which promotes the reduction of the band gap, the increase of active sites, the acceleration of charge separation and migration, and the increase of the hydrogen evolution rate of the photocatalyst.
[0006] The purpose of the present invention is to provide a composite photocatalyst based on carbon nitride surface interface modification.
[0007] The first technical solution adopted by the present invention is a method for preparing a composite photocatalyst based on surface modification of carbon nitride, and the specific operation steps are as follows:
[0008] Step 1: gradually add KOH solution to urea solution, stir and mix evenly, then heat the obtained mixture and freeze-dry it to obtain g-C3N 4-x Precursor;
[0009] Step 2: g-C3N 4-x The precursor is further heat treated at high temperature to obtain g-C3N 4-x Sample, where x ranges from 0 to 1;
[0010] Step 3, deionized water, Ni(NO3)2·6H2O and urea are mixed, stirred and then subjected to high temperature treatment, cooled and then washed, and finally flower-shaped Ni(OH)2 is obtained under drying conditions;
[0011] Step 4: g-C3N 4-x The sample and flower-like Ni(OH)2 were dispersed in deionized water, dried and washed, and dried again to synthesize Ni(OH)2 / g-C3N 4-x Composite materials.
[0012] The present invention is also characterized in that:
[0013] Furthermore, in step 1, stirring is performed for no less than 30-35 minutes.
[0014] Furthermore, in step 1, the concentration of the KOH solution is 0.02-0.025 mmol·L -1 , urea solution concentration is 3.15-3.2mmol·L -1 ; The volume ratio of the KOH solution to the urea solution is 1:21.
[0015] Furthermore, in step 1, the specific steps of heating the mixture and then freeze-drying it are: treating it at 120° C. for 6-6.5 hours in a stainless steel autoclave, and then freeze-drying it in an ice ethanol bath at -80° C.
[0016] Furthermore, in step 2, g-C3N 4-x The precursor was treated at 550°C for 2-2.5 hours and sealed with tin foil.
[0017] Furthermore, in step 3, the concentration of Ni(NO3)2·6H2O in the mixed dispersion is 0.18-0.22 mmol, and the concentration of urea is 0.45-0.55 mmol; the high temperature treatment in step 3 is carried out in a stainless steel autoclave at 120°C for 12-12.5 hours, and after cooling to room temperature, it is washed alternately with deionized water and ethanol three times, and finally vacuum dried at 60°C.
[0018] Further, in step 4, the g-C3N 4-xThe mass ratios of the sample to the flower-shaped Ni(OH)2 prepared in step 3 are 100:1, 100:3, 100:5, 10:1, and 100:15, respectively;
[0019] Furthermore, the drying temperature of step 4 is 70°C, and the washing method after drying is: washing with deionized water and ethanol alternately for 3 times; and finally drying at 60°C.
[0020] The second technical solution adopted by the present invention is: a composite photocatalyst based on carbon nitride surface modification is obtained by using a composite photocatalyst preparation method based on carbon nitride surface modification. 4-x The composite material has good photocatalytic performance. The introduction of nitrogen defects and the modification of Ni(OH)2 produce a synergistic effect, which improves the charge separation and migration efficiency of the material. The formed two-dimensional / two-dimensional heterojunction structure provides an efficient transmission channel for photogenerated carriers, inhibits the recombination of electron-hole pairs, and improves the utilization efficiency of photogenerated carriers. Ni(OH)2 is evenly distributed in g-C3N 4-x The surface provides more active sites, which is conducive to the photocatalytic reaction. At the same time, the composite material broadens the light absorption range and improves the stability and repeatability of the photocatalyst, showing its structural and performance advantages.
[0021] The application of the composite photocatalyst based on carbon nitride surface interface modification is specifically as follows: the photocatalyst is used to perform photocatalytic hydrogen evolution.
[0022] The beneficial effects of the present invention are:
[0023] The present invention constructs Ni(OH)2 / C3N 4-x 2D / 2D heterojunction, and its photocatalytic hydrogen evolution performance was studied. 4-x The nanocomposite material exhibited an excellent photocatalytic hydrogen evolution rate of 5590 μmol·g-1·h-1. Compared with the original g-C3N4, its hydrogen evolution activity was increased by 39.4 times; 4-x , and also increased by 18.8 times. This significant performance improvement is due to the synergistic effect of the introduction of nitrogen defects and the modification of Ni(OH)2, which makes the composite material more efficient in the photocatalytic hydrogen evolution reaction. At the same time, the composite material can effectively promote the separation and migration of photogenerated carriers, improve the utilization efficiency of photogenerated carriers, and thus promote the hydrogen evolution reaction. The composite material improves the light absorption capacity in the visible light region and provides abundant active sites. At the same time, it can maintain efficient photocatalytic hydrogen evolution ability after multiple uses, reducing the cost of use and improving its application potential in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] FIG. 1( a ) is an XRD diffraction pattern of the sample prepared in Example 1-4 of the present invention.
[0025] FIG. 1( b ) is a FTIR spectrum of samples prepared in Examples 1-4 of the present invention.
[0026] Figure 2 This is the HRTEM image of the sample prepared in Example 4 of the present invention.
[0027] FIG3( a ) is an XPS spectrum of N1s of the sample prepared in Example 2-4 of the present invention.
[0028] FIG3( b ) is an XPS spectrum of O1s of the sample prepared in Example 3-4 of the present invention.
[0029] FIG3( c ) is a Zeta potential diagram of the samples prepared in Examples 2-4 of the present invention.
[0030] FIG. 4( a ) is a UV-visible spectrum of the samples prepared in Examples 1-4 of the present invention.
[0031] FIG4( b ) is an optical band gap diagram of the sample prepared in Example 1-2 of the present invention.
[0032] FIG. 5( a ) is a graph showing the photocurrent density of samples prepared in Examples 1-4 of the present invention.
[0033] FIG5( b ) is an interface impedance diagram of samples prepared in Examples 1, 2, and 4 of the present invention.
[0034] FIG5( c ) is a PL spectrum diagram of the samples prepared in Examples 1, 2, and 4 of the present invention.
[0035] FIG. 6( a ) is a graph showing the photocatalytic hydrogen evolution rates of samples prepared in Examples 1-4 of the present invention.
[0036] FIG6( b ) is a cycle test diagram of the sample prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0037] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0038] Example 1
[0039] The crucible containing 10 g of urea was tightly sealed with tin foil, and then the sample was heated in air at 550 °C for 2 h. The resulting bulk g-C3N4 sample was obtained by allowing the sample to cool naturally.
[0040] Example 2
[0041] First, 1 mL of 0.02-0.025 mmol·L -1 KOH solution was added dropwise to 21 mL with a concentration of 3.15-3.2 mmol·L -1 The resulting homogeneous mixture was then sealed in a polytetrafluoroethylene-lined stainless steel autoclave and treated at 120 °C for 6-6.5 h. g-C3N can be obtained from the hydrothermal solution after freeze drying in an ice-ethanol bath at -80 °C. 4-x Finally, g-C3N 4-x The precursor was further treated at 550 °C with tin foil for 2-2.5 h to obtain chiffon-like g-C3N 4-x sample.
[0042] Example 3
[0043] First, 0.18-0.22mmol Ni(NO3)2·6H2O and 0.45-0.55mmol urea were added to 50mL deionized water. The mixture was stirred for 30-35 minutes, and NH3·H2O (mass fraction of 28%) was slowly added dropwise under strong stirring. Once the solution turned light blue, the resulting mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and treated at 120°C for 12-12.5h. After cooling to room temperature, vacuum filtration was performed, followed by alternating washing with deionized water and ethanol three times, and finally vacuum dried at 60°C to obtain a flower-like Ni(OH)2 sample.
[0044] Example 4
[0045] On the basis of Examples 2 and 3, 0.95-1.05 g g-C3N 4-x The sample and a certain amount of Ni(OH)2 (g-C3N in mass ratios of 100:1, 100:3, 100:5, 10:1, and 100:15) 4-x The sample and flower-shaped Ni(OH)2) were ultrasonically dispersed in 15-25 mL of deionized water and then completely dried at 70°C. The obtained sample was washed three times with deionized water and ethanol alternately. Finally, the sample was vacuum dried at 60°C, ground and collected for later use. According to the different content of Ni(OH)2, different mass ratios of Ni(OH)2 / g-C3N can be prepared. 4-x Composite materials.
[0046] Example 5
[0047] Based on Examples 2 and 3, g-C3N 4-xThe sample and flower-like Ni(OH)2 were dispersed in deionized water, dried at 70°C, and washed three times with deionized water and ethanol alternately; finally, Ni(OH)2 / g-C3N was synthesized by drying again at 60°C. 4-x Composite material; g-C3N 4-x The mass ratio of the sample to flower-shaped Ni(OH)2 is 100:1.
[0048] Example 6
[0049] Step 1: add 0.02-0.025 mmol·L -1 The KOH solution was gradually added dropwise to a concentration of 3.15-3.2 mmol·L -1 The volume ratio of KOH solution to urea solution was 1:21; the mixture was stirred for 35 min, and then treated in a stainless steel autoclave at 120 °C for 6-6.5 hours, and then freeze-dried in an ice ethanol bath at -80 °C to obtain g-C3N 4-x Precursor;
[0050] Step 2: g-C3N 4-x The precursor was treated at 550 °C for 2-2.5 hours to obtain g-C3N 4-x sample;
[0051] Step 3, deionized water, Ni(NO3)2·6H2O and urea are mixed, wherein the concentration of Ni(NO3)2·6H2O in the mixed dispersion is 0.2 mmol, and the concentration of urea is 0.5 mmol; after stirring, the mixture is treated in a stainless steel autoclave at 120° C. for 12 hours, and after cooling, the mixture is washed alternately with deionized water and ethanol three times, and finally dried in vacuo at 60° C. to obtain flower-shaped Ni(OH)2;
[0052] Step 4: g-C3N 4-x The sample and flower-like Ni(OH)2 were dispersed in deionized water, dried and washed, and dried again to synthesize Ni(OH)2 / g-C3N 4-x Composite materials.
[0053] The XRD and FTIR spectra of the samples obtained in Comparative Examples 1-4 are shown in Figure 1(a). 4-x The characteristic peaks corresponding to Ni(OH)2 appeared in 5%-Ni(OH)2 / C3N 4-x The spectrum of 2176 cm-1 in Figure 1(b) proves that the g-C3N4 structure in the composite material is retained and Ni(OH)2 is successfully introduced. -1A new characteristic peak appears at 5%-Ni(OH) / C3N. This peak is due to the reaction between OH- in KOH and -NH in urea. This reaction process leads to the generation of nitrogen defects. 4-x In the spectrum of -1 The characteristic peak at corresponds to the characteristic signal peak of Ni(OH), which indicates that Ni(OH) has been successfully introduced into g-C3N 4-x surface.
[0054] Figure 2 The Ni(OH)2 / g-C3N prepared in Example 4 of the present invention 4-x Composite materials, from which lattice fringes can be clearly observed, and by measuring the spacing of the lattice fringes, the crystal structure information of the material can be determined. For Ni(OH), the lattice spacing is 0.23nm, corresponding to its (101) crystal plane; for g-C3N 4-x The lattice spacing is 0.32nm, corresponding to its (110) crystal plane. The existence and structural characteristics of the two components in the composite material were further confirmed, indicating that Ni(OH)2 / g-C3N was successfully synthesized. 4-x Composite materials, and the two materials are closely combined at the microscopic level.
[0055] XPS images of the samples obtained in Comparative Examples 2-4
[0056] In Figure 3(a), 5%-Ni(OH)2 / C3N 4-x In the XPS N 1s spectrum of the composite material, the N 1s peak moves toward a higher binding energy, which indicates that the electron cloud density around the nitrogen atoms has changed in the composite material. The electron cloud density around the nitrogen atoms has changed. Combined with other characterization results, as shown in Figure 3(b), this change in electron cloud density is due to the electrons from g-C3N 4-x This result confirms that Ni(OH)2 and g-C3N in the composite material 4-x There is a strong interaction between them, which affects the electronic structure of the material through electron transfer, which is of great significance to the photocatalytic performance of the composite material, helps to promote the separation and transfer of photogenerated carriers, and improves the photocatalytic activity. 4-x With a more negative potential, while Ni(OH)2 has a higher positive potential, there is an electrostatic attraction between them. This electrostatic interaction enhances their affinity, allowing Ni(OH)2 to be adsorbed onto g-C3N 4-x surface, realizing the electrostatic self-assembly process.
[0057] Optical properties and band structures of samples obtained in comparison with Examples 1-4
[0058] Figure 4(a) shows that g-C3N 4-x Compared with the original g-C3N4, the absorption edge has red shifted. This means that g-C3N 4-x It can absorb light with longer wavelengths, and its absorption range extends to the visible light region. 4-x It can absorb more photons to generate photogenerated carriers, and the heterojunction structure provides an efficient transmission channel for these photogenerated carriers, promotes the separation of electrons and holes, reduces their recombination probability, and is conducive to increasing the rate of hydrogen evolution reaction. Figure 4 (b) shows that the band gap of g-C3N4 is 2.95eV, while g-C3N 4-x The band gap of g-C3N4 is 2.74eV. This result accurately reflects the effect of the introduction of nitrogen defects on the electronic structure of g-C3N4, which leads to a narrowing of the band gap. The narrowing of the band gap and the red shift of the absorption edge make g-C3N4 4-x It can absorb more photons and generate more photogenerated carriers (electron-hole pairs), providing more sufficient reaction power for the photocatalytic reaction. After forming a composite material with Ni(OH)2, this light absorption ability and the heterojunction structure promote the separation and transmission of photogenerated carriers, and together improve the photocatalytic activity of the composite material.
[0059] Electrochemical Characterization and Photocatalytic Hydrogen Evolution Test of the Samples Obtained from Comparative Examples 1-4
[0060] 5% Ni(OH)2 / g-C3N in Figure 5(a) 4-x The higher photocurrent density means that the photogenerated electrons and holes can be separated more effectively, thereby reducing the recombination of electrons and holes. 4-x The composite material has the lowest interface impedance value, and the transmission resistance of photogenerated carriers at the interface of the composite material is small, which can migrate more quickly and is beneficial to improving the efficiency of the photocatalytic reaction. The PL spectrum intensity of Figure 5(c) is usually related to the recombination rate of charge carriers. The stronger the intensity, the higher the recombination rate of charge carriers; the weaker the intensity, the slower the recombination rate of charge carriers. This further proves that 5% Ni(OH)2 / g-C3N 4-x The composite material has a slower charge carrier recombination rate, which improves the photocatalytic activity and charge transport rate.
[0061] Photocatalytic hydrogen production performance and cycle test of samples obtained in comparative examples 1-4
[0062] Figure 6(a) shows that g-C3N 4-x The hydrogen evolution rate is higher than that of g-C3N4. After loading Ni(OH)2, the rate increases first and then decreases with the increase of its content, reaching the highest value (5590 μmol·g -1·h -1 ), g-C3N4 and g-C3N 4-x 39.4 and 18.8 times of that of the composite material 5% Ni(OH)2 / g-C3N 4-x It has excellent hydrogen production performance. Figure 6(b) shows that the composite material 5% Ni(OH)2 / g-C3N prepared in Example 4 4-x After five cycles (10 h) of testing, no significant degradation was observed, indicating its excellent photocatalytic stability.
[0063] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a composite photocatalyst based on surface modification of carbon nitride, characterized in that: The specific steps are as follows: Step 1: gradually add KOH solution to urea solution, stir and mix evenly, then heat the obtained mixture and freeze-dry it to obtain g-C3N 4-x Precursor; Step 2: g-C3N 4-x The precursor is further heat treated at high temperature to obtain g-C3N 4-x Sample, where x ranges from 0 to 1; Step 3, deionized water, Ni(NO3)2·6H2O and urea are mixed, stirred and then subjected to high temperature treatment, cooled and then washed, and finally flower-shaped Ni(OH)2 is obtained under drying conditions; Step 4: g-C3N 4-x The sample and flower-like Ni(OH)2 were dispersed in deionized water, dried and washed, and dried again to synthesize Ni(OH)2 / g-C3N 4-x Composite materials.
2. The method for preparing a composite photocatalyst based on carbon nitride surface modification according to claim 1, characterized in that: In step 1, stir for no less than 30-35 minutes.
3. The method for preparing a composite photocatalyst based on surface modification of carbon nitride according to claim 1, characterized in that: In step 1, the concentration of the KOH solution is 0.02-0.025 mmol·L -1 , urea solution concentration is 3.15-3.2mmol·L -1 ; The volume ratio of the KOH solution to the urea solution is 1:
21.
4. The method for preparing a composite photocatalyst based on carbon nitride surface modification according to claim 1, characterized in that: In step 1, the specific steps of heating the mixture and then freeze-drying it are: treating it at 120° C. for 6-6.5 hours in a stainless steel autoclave, and then freeze-drying it in an ice ethanol bath at -80° C.
5. The method for preparing a composite photocatalyst based on surface modification of carbon nitride according to claim 1, characterized in that: In step 2, g-C3N 4-x The precursor was treated at 550°C for 2-2.5 hours and sealed with tin foil.
6. The method for preparing a composite photocatalyst based on carbon nitride surface modification according to claim 1, characterized in that: In step 3, the concentration of Ni(NO3)2·6H2O in the mixed dispersion is 0.18-0.22 mmol, and the concentration of urea is 0.45-0.55 mmol; the high temperature treatment in step 3 is to treat at 120°C in a stainless steel high pressure sterilizer for 12-12.5 hours, cool to room temperature, wash three times with deionized water and ethanol alternately, and finally dry in vacuum at 60°C.
7. The method for preparing a composite photocatalyst based on surface modification of carbon nitride according to claim 1, characterized in that: In step 4, the g-C3N 4-x The mass ratios of the sample to the flower-shaped Ni(OH)2 prepared in step 3 are 100:1, 100:3, 100:5, 10:1, and 100:15, respectively; The drying temperature in step 4 is 70° C., and the washing method after drying is: washing with deionized water and ethanol alternately for 3 times; and finally drying at 60° C.
8. A composite photocatalyst based on carbon nitride surface modification obtained by the preparation method according to any one of claims 1 to 7.
9. The specific application of the composite photocatalyst based on carbon nitride surface modification according to claim 8 is as follows: using the photocatalyst to carry out photocatalytic hydrogen evolution.